2018
DOI: 10.1017/neu.2017.39
|View full text |Cite
|
Sign up to set email alerts
|

A brief history of antidepressant drug development: from tricyclics to beyond ketamine

Abstract: Firstly, we review how the pharmacological treatment for major depression started, and we point out the main drugs discovered, the researchers involved, and how the studies developed have contributed to the understanding of the neurobiology of depression. Secondly, the major problems regarding the clinical efficacy and acceptance of these drugs are discussed, and the introduction of the glutamatergic system as a target for antidepressant drugs is presented. Finally, we review how ketamine revealed itself as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 140 publications
(195 reference statements)
0
55
0
1
Order By: Relevance
“…(2) blocking NMDA receptors and activating α-amino -3-hydroxy-5-methyl-4-isoxazolpropionic acid receptor (AMPAR); 154 (3) reducing the inhibition of the presynaptic glutamatergic pathway by inhibiting the activity of GABA's effect, leading to increased glutamate release in the presynaptic membrane; 155 and (4) upregulating the expression level of BDNF. 156 By studying the mechanism of ketamine, it is not difficult to observe that some components of JZG have similar antidepressant mechanisms as ketamine.…”
Section: The Pharmacological Mechanism Of Jzg In the Treatment Of Depmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) blocking NMDA receptors and activating α-amino -3-hydroxy-5-methyl-4-isoxazolpropionic acid receptor (AMPAR); 154 (3) reducing the inhibition of the presynaptic glutamatergic pathway by inhibiting the activity of GABA's effect, leading to increased glutamate release in the presynaptic membrane; 155 and (4) upregulating the expression level of BDNF. 156 By studying the mechanism of ketamine, it is not difficult to observe that some components of JZG have similar antidepressant mechanisms as ketamine.…”
Section: The Pharmacological Mechanism Of Jzg In the Treatment Of Depmentioning
confidence: 99%
“… 152 Ketamine, as an N-methyl-D-aspartic acid (NMDA) receptor antagonist, has a different mechanism from traditional5-HT reuptake inhibitors, which provides a new target for the development of novel antidepressants. 153 Ketamine may play an antidepressant role through a variety of mechanisms, including (1) blocking the effect of glutamate on NMDA receptors; (2) blocking NMDA receptors and activating α-amino-3-hydroxy-5-methyl-4-isoxazolpropionic acid receptor (AMPAR); 154 (3) reducing the inhibition of the presynaptic glutamatergic pathway by inhibiting the activity of GABA’s effect, leading to increased glutamate release in the presynaptic membrane; 155 and (4) upregulating the expression level of BDNF. 156 By studying the mechanism of ketamine, it is not difficult to observe that some components of JZG have similar antidepressant mechanisms as ketamine.…”
Section: The Pharmacological Mechanism Of Jzg In the Treatment Of Depmentioning
confidence: 99%
“…The mechanisms of action by which ketamine exerts its rapid effects have been the subject of interest by many research groups, which have prospectively shown that the molecular targets for ketamine's effects go beyond the antagonism of NMDA receptors. 36 Notably, ketamine's rapid action seems to be triggered by antagonism of NMDA receptors in GABAergic interneurons, preventing the inhibitory action of this system on glutamatergic tonus. 37 In turn, glutamatergic neurons release glutamate in the synaptic cleft, which preferentially activates AMPA (alpha-amino-3-hydroxy-methyl-5-4-isoxazole propionic acid) receptors.…”
Section: Mechanisms Underlying the Fast-acting Antidepressant Effect mentioning
confidence: 99%
“…In 1945, Hä fliger & Schinder synthesized G22355 (imipramine). 3 Since its chemical structure was similar to that of chlorpromazine, it was tested for antipsychotic properties, but was ineffective in schizophrenia. However, imipramine had unexpected antidepressant properties: among patients with different psychiatric disorders, those with severe depression and psychomotor retardation experienced remarkable improvement after several weeks of daily treatment with imipramine, the first tricyclic antidepressant (TCA).…”
mentioning
confidence: 99%